Pre-emptive Allogeneic Hematopoietic Stem Cell Transplantation in Ataxia Telangiectasia - Bakhtiar, Shahrzad; Woelke, Sandra; Huenecke, Sabine; Kieslich, Matthias; Taylor, Alexander Malcolm; Schubert, Ralf; Zielen, Stefan; Bader, Peter (Frontiers in Immunology, 2018)
Ataxia telangiectasia (A-T) is a primary immunodeficiency with mutations in the gene encoding the A-T mutated (ATM) protein that interacts with immune, hematopoietic, and endocrine targets resulting in broad multi-systemic clinical manifestations with a devastating outcome. Apart from a progressive neurodegenerative disorder, A-T leads to significantly increased susceptibility to malignancies. It is a matter of discussion whether pre-emptive allogeneic hematopoietic stem cell transplantation (alloHSCT) using a reduced intensity conditioning regimen would be an option to restore immune-competence and prevent malignancy, as shown in animal models, because conventional treatment protocols of malignant diseases using radio- and/or chemotherapy have a high rate of therapy-related morbidity and mortality in these patients. We present the course of the disease, including immune reconstitution and neurological outcome following pre-emptive alloHSCT in a four-year-old boy with A-T on a six year follow-up. Our manuscript provides a proof-of-concept of alloHSCT as an individual pre-emptive treatment strategy from which some A-T patients might benefit.